Should Congress Pass the Employee Free Choice Act? Some Neighborly Advice - Godard, John; Rose, Joseph B; Slinn, Sara (Just Labour, 2009)
American labour law is broken. As many as 60 percent of American workers would like to have a union, yet only 12 percent actually do. This is largely due to systematic employer interference, often in violation of existing laws. The Employee Free Choice Act (EFCA), currently before Congress, contains provisions to rectify this problem. Canada’s experience with similar provisions can be helpful in evaluating the arguments surrounding this act. It suggests that the reforms proposed in EFCA can be expected to safeguard rather than deny employees’ free choices. They will not alter the balance of power in collective bargaining, but only help to ensure that workers can exercise their basic right to meaningful representation at work and, potentially, to win gains that could help to reduce inequality and return America to prosperity.